2016
DOI: 10.1136/bmj.i2923
|View full text |Cite
|
Sign up to set email alerts
|

Differences in incomes of physicians in the United States by race and sex: observational study

Abstract: Objectives To estimate differences in annual income of physicians in the United States by race and sex adjusted for characteristics of physicians and practices.Design Cross sectional survey study.Setting Nationally representative samples of US physicians.Participants The 2000-13 American Community Survey (ACS) included 43 213 white male, 1698 black male, 15 164 white female, and 1252 black female physicians. The 2000-08 Center for Studying Health System Change (HSC) physician surveys included 12 843 white male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
106
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 14 publications
(27 reference statements)
10
106
0
1
Order By: Relevance
“…1,2 In 2017, 21.2% of fellows and 35.1% of ophthalmology trainees were female in the Royal Australian & New Zealand College of Ophthalmologists (RANZCO). 3 Studies around the world have found that female doctors earn less than their male counterparts, even after accounting for number of hours worked, [4][5][6][7][8] and female ophthalmologists report doing less procedural work than their male counterparts. 9,10 Few studies have been conducted investigating the differences in practice patterns, social circumstances and remuneration between female and male ophthalmologists in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In 2017, 21.2% of fellows and 35.1% of ophthalmology trainees were female in the Royal Australian & New Zealand College of Ophthalmologists (RANZCO). 3 Studies around the world have found that female doctors earn less than their male counterparts, even after accounting for number of hours worked, [4][5][6][7][8] and female ophthalmologists report doing less procedural work than their male counterparts. 9,10 Few studies have been conducted investigating the differences in practice patterns, social circumstances and remuneration between female and male ophthalmologists in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Most health systems show horizontal (confined to certain specialties) and vertical (confined to lower levels) ‘segregation’ of women doctors . Further, women doctors earn less than men, even when corrected for hours of work, specialty and age . Women are over‐represented in specialties, such as general practice, paediatrics, and obstetrics and gynaecology, and under‐represented in surgical specialties and in senior leadership positions .…”
Section: Contextmentioning
confidence: 99%
“…Particularly in relation to underserved populations, there is a significant difference in average income and education between physicians and their patients [18], and many physicians do not live in the communities where they work. The effects of systemic poverty and stigma can also create a distance that makes it hard to recognize our connection to each other.…”
Section: Geographic and Professional Dividesmentioning
confidence: 99%